Treatment of meat industry wastewater using coagulation and Fenton's reagent = Oczyszczanie ścieków zakładów mięsnych w procesie koagulacji i z zastosowaniem odczynnika Fentona - Kwarciak-Kozłowska, Anna; Bohdziewicz, Jolanta; Mielczarek, Karolina; Krzywicka, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the paper was to study meat industry wastewater treatment efficiency during chemical processes. The research was carried out in two steps. The first step was the coagulation process and the second step was the Fenton reaction. It was found that wastewater treatment with the use of Fenton's reagent achieved a higher degree of removal of the pollutants determined as COD, TOC and TN in comparison to the coagulation of PIX 113.
Keywords: oczyszczanie ścieków; koagulacja; odczynnik Fentona; zakłady mięsne; meat industry wastewater; coagulation process; Fenton process; PIX 113; PAX XL 19